The Determinants of Regional Price Discrimination in the Telecommunication Industry: An Empirical Study of 31 Provinces and Municipalities in China - He, Xiaohong; Wang, Guipu (Journal of Comparative International Management)

(untitled) (Management Futures, 2016)
Telecommunication prices are vastly different across regions in China. This paper aims to identify the determinants that affect regional pricing behavior of China telecom operators. Using regional telecommunication data of 31 provinces and autonomous regions in China (excluding Hong Kong and Macao) during 2002–2011, we identified several factors which affect the regional price differences. The findings provide insights on the working of China telecommunication industry and have implications for firms' marketing strategies and government policies.